WORKING CAPITAL RELATIONSHIP WITH FIRM PROFITABILITY AND SIZE - Muhammad Ahsan Kabir; Azeddine Elalami Lahlimi; Abdulmalik Muhammad Junaidu; Issah Sham-Una; Muneeb Ahmad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Working Capital (WC) turnover as far as days has been viewed as a valuable proportion of company's powerful liquidity and money the board. This investigation was directed through the plan to inspect the connection of the WC through the size as well as advantage of the businesses in the four explicit accumulated areas evidenced on Karachi Stock Exchange to be specific Petroleum Limited, Engineering Works, Textile Mills, and Garments manufacturers. The knowledge was collected recognizing with the 40 tested organizations out of the aggregate in the related parts for example 185 covering the time of 2016-2019 by using ANOVA analysis and Pearson’s correlation test. This examination in attendance informs documentation of the assessment about the issue of money the board a zone that isn't especially explored ahead in the generated nations similar to Pakistan. The current examination includes different supportive consequences that ought to be practiced for the account directors, manufacturing organizations, educationists and specialists.